The Symbols Used in Internet Chatting: A Semiotic Analysis - Sri Mulyani (IAIN Salatiga, 2009)
The aims of this research is to describe the kind of symbols used on internet chatting. Besides elaborating the relation between the symbol and the signee. And the last one of study is to describe the meaning of the symbols used in internet chatting. Since the research explores the symbols used in the internet chatting, qualitative approach is deemed to be the precise research design. The data obtained are described comprehensively by classifying the symbols, analyzing the representation of the symbols based on semiotic approach, and interpreting the meaning of symbols based on the context of the internet chatting text. The findings show that the symbols consists of number, letter, combination of number and letter, and the emoticons or smiley. The sample of the number, consist of ‘2’ and ‘4’. For the letter consist of ‘R’, ‘U’, ‘b’, ‘Ur’, ‘ASL’, ‘btw’, and so on. For emoticons consist of ‘:-)’, ‘:-(‘, ‘:-P’, ‘:-D’, ‘:-C’, ‘;-)’, ‘:- ))’, ‘: ’, ‘|-)’, ‘(-_-)’, ‘^_^’, ‘:-|’, and ‘8-O’. Those symbols have different meaning or references with different interpreters because they can be interpreted in denotative level as signifier or in connotative level as signified.Keywords: symbols; internet; chatting; semiology